PENGARUH KESADARAN WAJIB PAJAK, SANKSI PERPAJAKAN, SISTEM ADMINISTRASI PERPAJAKAN MODERN, PENGETAHUAN KORUPSI, DAN TAX AMNESTY TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA SEMARANG - Ristra Putri Ariesta; Lyna Latifah (Universitas Sarjanawiyata Tamansiswa, 2017)
Taxpayer compliance is a situation where the taxpayer complies the entire obligation and commit the tax due. The Government's efforts in improving taxpayer compliance are the intensification and extensification taxes. The purpose of this research was to find out whether or not there is the influence of the tax payers consciousness, the tax penalties, the modern Tax Administration System, the knowledge of corruption and the tax amnesty toward the taxpayer compliance in KPP PratamaCandisari, Semarang.The population in this research totalled 67.453 taxpayers. The technique of sampling done by the method of convenience sampling with 120 sample taxpayers. The method to collecting the data used questionnaire. The data were analyzed using descriptive statistics and regression analysis.used descriptive and multiple regression analysis. The result of this research showed that there is a significant influence of the taxpayer consciousness toward the taxpayer compliance 9.36%, tax penalties toward the taxpayer compliance 6.05%, the modern tax administration system toward the taxpayer compliance 4.97%, and the knowledge of corruption toward the taxpayer compliance 5.90%. The conclusion of this research showed that there is the influence of the taxpayer consciousness, tax penalties, the modern tax administration system, the knowledge of corruption and the tax amnesty toward the tax compliance. It is suggested that KPP PratamaCandisari conducts the tax socialization or the elucidation intensively and incessantly in order to increase the understanding of the tax amnesty and the taxpayer consciousness or society to the importance of paying the tax proper to amount and on time. The next researcher examines with the different object and adds another variable to find out the other factors which influence the taxpayer compliance.Keywords:Tax Payer Consciousness, Tax Penalties, Modern Tax Administration System, Knowledge of Corruption, Tax Amnesty, Taxpayer Compliance